(5x + 6y + 8) + 3(3x - 2y + 16) = 0 + 3(0) (add 3 times the second equation to the first)

5x + 6y + 8 + 9x - 6y + 48 = 0 (eliminate parentheses)

14x + 56 = 0 (collect terms)

x + 4 = 0 (divide by 14)

x = -4 (subtract 4)

3(-4) - 2y + 16 = 0 (substitute for x in the second equation)

4 - 2y = 0 (collect terms)

2 - y = 0 (divide by 2)

2 = y (add y)

The solution is

5x + 6y + 8 + 9x - 6y + 48 = 0 (eliminate parentheses)

14x + 56 = 0 (collect terms)

x + 4 = 0 (divide by 14)

x = -4 (subtract 4)

3(-4) - 2y + 16 = 0 (substitute for x in the second equation)

4 - 2y = 0 (collect terms)

2 - y = 0 (divide by 2)

2 = y (add y)

The solution is

**(x, y) = (-4, 2)**.